ETIKA KONSUMSI DALAM PERSPEKTIF EKONOMI ISLAM - Andi Bahri S. (State Institute of Islamic Studies (IAIN) Palu, 2014)
This paper deals with consumption behavior in society; how to consume as recommended by Islam; and how should consumption behavior in the view of Islamic economics. Based on the results of the analysis, we concluded as follows: 1) Consumption behavior should pay attention to the aspects of the categories of needs asprimary needs, secondary needs and tertiary needs in accordance with the spirit of al-maqāṣd al-syarī’ah. In the view of Islam, consumption behavior should avoid isrāf and tabżīr behavior in using their income to meet their life needs. In the aspect of comsuming any kind of food, the Muslims should always comsume the halal and the toyyib food. Consumption behavior in Islamic economics aims at achieving both the aspect of material and the aspect of spriruality, these two aspects will be achieved by maximizing the value of the use of each item in consumption.Kata kunci: Perilaku konsumsi, kebutuhan, keingingan, ekonomi Islam